Criança, leitura e tecnologia: relação, diálogo e reflexão - Martins, Délys Louise de Lima [UNESP] (Universidade Estadual Paulista (Unesp), 2021)
This research work seeks to reflect on the presence of reading in Early Childhood Education. The function and importance of reading has been a theme widely explored in the school context as a tool for training children during the literacy process in early childhood education. The practice of reading as a fundamental right of individuals specifically provides children aged three to five with the possibility of developing important aspects such as language - verbal and written - and linguistic intelligence.In this learning process, the practice of reading creates situations of knowledge of the world that go beyond everyday experience.The teacher, as a mediator of the practices and experiences of the literacy process in Early Childhood Education, needs to be aware of the reading context in which these children are already inserted and expand their perception of both everyday signs and symbols and linguistic signs, the word inserted in the social and cultural context. In the context of a world in which communication is also processed through information technology (tablets, computers, interactive televisions and many others), providing different situations and new challenges for children, it becomes necessary to rethink reading practices in schools, aiming at the need to train individuals not just able to act in today’s society, but to think in their own world. Considering, therefore, reading as a fundamental instrument for the formation of the individual and technology as a necessary instrument for human development, this study aims to investigate how reading contributes to the emancipation of the child's mind in the current technological cultural context. We draw on the thought of Lev Vygotsky (1984) on the cognitive development of children aged three to five years. We will also refer to the thoughts of Paulo Freire (1981), Antonio Candido (1995), Magda Soares (2001) and Nelly Novaes Coelho (2000), on the issue of reading since the individual's early years, its importance in their development and how it is present in the formation of human beings. On the technological context of reading, we will seek references in the studies of Roger Chartier (2017) and Pierre Lévy (1999) to reflect the space of reading in today's technology. Finally, we will make some suggestions for practical reading activities linked to digital. We will use exploratory research as a methodology, based on bibliographical research, seeking to build a dialogue between authors in the search for reflection on the contribution of reading to the education of children for the current cultural context.

Este trabalho de pesquisa busca refletir sobre a presença da leitura na Educação Infantil. A função e a importância da leitura tem sido um tema muito explorado no contexto escolar como instrumento de formação das crianças durante o processo do letramento no ensino infantil. A prática de leitura como direito fundamental dos indivíduos fornece, especificamente, às crianças de três a cinco anos a possibilidade de desenvolverem aspectos importantes como a linguagem - verbal e escrita - e a inteligência linguística. Nesse processo de aprendizagem, a prática da leitura cria situações de conhecimento de mundo que vão além da experiência cotidiana. O professor, como mediador das práticas e das vivências do processo do letramento na Educação Infantil, necessita estar atento ao contexto leitor no qual essas crianças já estão inseridas e ampliar sua percepção, tanto dos sinais e símbolos do cotidiano como dos signos linguísticos, da palavra inserida no contexto social e cultural. No contexto de um mundo em que a comunicação também se processa por meio da tecnologia da informação (tablets, computadores, televisores interativos e muitos outros), proporcionando diferentes situações e novos desafios para as crianças, faz-se necessário repensar as práticas de leitura nas escolas, tendo em vista a necessidade de formar indivíduos não só capazes de atuarem na sociedade atual, mas de pensarem o seu próprio mundo. Considerando, portanto, a leitura como instrumento fundamental de formação do indivíduo e a tecnologia como instrumento necessário para o desenvolvimento humano, este estudo tem como objetivo investigar como a leitura contribui para a emancipação da mente da criança no atual contexto cultural tecnológico. Valemo-nos do pensamento de Lev Vygotsky (1984) sobre o desenvolvimento cognitivo da criança, de três a cinco anos. Também iremos nos reportar ao pensamento de Paulo Freire (1981), Antonio Candido (1995), Magda Soares (2001) e Nelly Novaes Coelho (2000), sobre a questão da leitura desde os anos iniciais do indivíduo, de sua importância no seu desenvolvimento e de como ela está presente na formação do ser humano. Sobre o contexto tecnológico da leitura, vamos buscar referências nos estudos de Roger Chartier (2017) e de Pierre Lévy (1999) para refletirmos o espaço da leitura na atualidade tecnológica. Finalizando faremos algumas sugestões de atividades práticas de leitura também vinculadas ao digital. Usaremos como metodologia a pesquisa exploratória, a partir de pesquisas bibliográficas, buscando construir um diálogo entre os autores na busca da reflexão sobre a contribuição da leitura para a formação das crianças para o contexto cultural atual.
Children, reading and technology: relationship, dialogue and reflection
Keywords: Reading; Children; Literacy; Technology; Leitura; Criança; Letramento; Tecnologia